(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know “the effect of the idea filtering strategy in Arabic grammar and critical thinking for fifth-grade literary students.” The researcher followed the experimental research method and chose an experimental design with partial control. The experimental group numbered (35) female students, and Division (A) the control group numbered (35) female students. Critical thinking according to the Watson and Claser test, consisting of (75) test items. Including the contribution of the current research in finding a solution to the problem of the low level of achievement and critical thinking among the students of the fifth literary grade, by presenting the material in a different and distinctive way, and that the use of ester The strategy of (filtering ideas) in Arabic grammar provides equal opportunities for all students to learn, as it addresses the issue of communicating information to all different groups and thus takes into account the individual differences between the students. In courses to inform them of the most important modern strategies, especially (the strategy of filtering ideas), and urging teachers to use modern strategies in teaching, especially the strategy of filtering ideas, and suggested conducting a similar study to the current study at other stages of study, and conducting a similar study of the study in other branches of the Arabic language.